ANALYSIS OF STUDENTS' ERRORS IN SOLVING MATHEMATICS PROBLEMS BASED ON THEIR CONCEPTUAL UNDERSTANDING - Nisa, Fairun; Haidar, Irajuana; Tahir, Tahir (Universitas Sembilanbelas November Kolaka, 2025)
This study aims to describe students' errors in solving mathematics problems based on their conceptual understanding. This research employed a descriptive qualitative approach involving 28 eighth-grade students from SMP Negeri 1 Latambaga. Data were collected using a conceptual understanding test, designed based on several indicators (classifying objects according to their properties, giving examples and non-examples of a concept, applying concepts algorithmically, and presenting concepts in various representative forms). Student errors were analyzed using Nolting's theory, which categorizes errors into careless, concept, application, and test procedure errors. The instrument was validated by mathematics education experts and teachers, and tested for item validity. After the test, four students representing different ability levels (high, medium, low, very low) were selected for interviews. The results showed that, in general, students' conceptual understanding was low. The most dominant errors were concept and application errors, while procedural and careless errors also appeared but less frequently. In conclusion, students' errors are primarily caused by weak conceptual understanding and a lack of systematic problem-solving abilities.